ZAWÓD DZIENNIKARZA W OBLICZU ZMIAN - Sobczak, Jacek; Kakareko, Ksenia (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The profession of journalism has changed recently. Nevertheless, it still requires professionalism and must be performed in accordance with professional ethics. Journalists use codes of ethics more to promote their own environment than to regulate journalistic behawior. In practice, journalists are often instrumental in the hands of the owners of newspapers, radio and television. The press is no longer the fourth power, but the only and most important authority. It raises the concern that journalists become available to the executive or the legislature. It’s a derivative of the fact that the employees employ the concept of “talent”, without requiring knowledge. As a result, alongside professional journalists, have been formed media workers and efficient information providers who don’t collect information for their publications themselves. The desire to meet the expectations of the audience on the one hand and the owners on the other hand, led to the resignation of objectivity, excessive attention to form and neglect of the content of the message. The functions of journalism began to evolve in a way incompatible with the interests of society. There are different types of journalism including neutral-objective and socially involved. The specialty of the profession of journalism becomes specialization. Specifying the status of the journalist, usually are distinguished an autonomous model and subordinate model. Contrary to the conviction of journalists, journalism is not a profession of public trust, nor a free profession. Journalists underline their professional “mission”, but they don’t notice that it is merely a service to the public.